A new petunia flower colour generated by transformation of a mutant with a maize gene - Meyer, P; Heidmann, I; Forkmann, G; Saedler, H (Nature (London), 1987)
Petunia hybrida is one of the classical subjects of investigation in plants in which the pathway of anthocyanin biosynthesis has been analysed genetically and biochemically. In petunia cyanidin- and delphinidin-derivatives, but no pelargonidin-derivatives are produced as pigments. This is due to the substrate specificity of the dihydroflavonol 4-reductase of petunia, which cannot reduce dihydrokaempferol. The petunia mutant RL01, which accumulates dihydrokaempferol, shows no flower pigmentation. RL01 served as a recipient for the transfer of the A1 gene of Zea mays encoding dihydroquercetin 4-reductase, which can reduce dihydrokaempferol and thereby provided the intermediate for pelargonidin biosynthesis. Transformation of RL01 with a vector p35A1, containing the A1-complementary DNA behind the 35S promotor leads to red flowers of the pelargonidin-type. Thus a new flower pigmentation pathway has been established in these plants.